Screening of the highly pathogenic Beauveria bassiana BEdy1 against Sogatella furcifera and exploration of its infection mode - Xiang, Xing; Yu, Siyuan; Ofori, Andrews Danso; Liu, Shuhua; Yang, Qunfang; Shang, Jing (Frontiers in Microbiology, 2024)
The white-backed planthopper (WBPH, Sogatella furcifera) is a notorious pest affecting rice production in many Asian countries. Beauveria bassiana, as the most extensively studied and applied insect pathogenic fungus, is a type of green and safe biological control fungus compared to chemical insecticides, and it does not pose the “3R” problem. In this study, the strain BEdy1, which had better pathogenicity to WBPH, was screened out from eight strains of B. bassiana. The daily growth rate, sporulation, and germination rate of BEdy1 strain were 3.74 mm/d, 1.37 × 108 spores/cm2, and 96.00%, respectively, which were significantly better than those of other strains. At a concentration of 1 × 108 spores/mL, the BEdy1 strain exhibited the smallest LT50 value (5.12 d) against the WBPH, and it caused the highest cumulative mortality and muscardine cadaver rates of the pest, which were 77.67 and 57.78%, respectively. Additionally, BEdy1 exhibited a significant time-dose effect on WBPH. This study further investigated the pathogenic process of BEdy1. The results showed that BEdy1 invaded by penetrating the body wall of the WBPH, with its spores mostly distributed in the insect’s abdominal gland pores, compound eyes on the head, and other locations. At 36 h, the germinated hyphae penetrated the insect’s body wall and entered the body cavity. At 84 h, the hyphae emerged from the body wall and accumulated in the insect’s abdomen, leading to a significant number of insect deaths at this stage. At 120 h, the hyphae entangled the insect’s compound eyes and produced new conidia on the insect’s body wall, entering a new cycle of infection. These findings indicate that BEdy1 has a strong infection ability against WBPH. In summary, this study provides a new highly pathogenic strain of B. bassiana, BEdy1, for the biological control of WBPH, which is of great significance for the green prevention and control of rice pests.